Practitioner's knowledge, attitudes, beliefs and practices towards urinary incontinence - Anika C. Janse van Vuuren; Jacobus A. van Rensburg; Susan Hanekom (AOSIS, 2023)
Background: One in three women in South Africa suffer from urinary incontinence. Effective management is influenced by patients help-seeking behaviour and services offered by healthcare professionals within the healthcare system. Current practice towards urinary incontinence management in South Africa is unknown. Objectives: Our study aimed to describe and compare urinary incontinence practice and knowledge of nurses and physicians (practitioners) working in primary healthcare settings, measured against the NICE 2013 guideline and explore attitudes and beliefs towards urinary incontinence management. Method: Cross-sectional study using a self-designed online questionnaire. All primary healthcare practitioners in the Western Cape were eligible for the study. Stratified random and snowball sampling was used. Data was analysed in consultation with a statistician using SPSS. Results: Fifty-six completed questionnaires were analysed. Practitioners had an overall knowledge score of 66.7% and practice score of 68.9% compared to NICE 2013 guidelines. A lack of knowledge regarding urinary incontinence screening, following up on patients and conducting bladder diaries were noted. Pelvic floor muscle training and bladder training education was recognised as initial management but only 14.8% of practitioners referred patients to physiotherapy. Half of the sample reported being uncomfortable with urinary incontinence, although the majority wanted to learn more about urinary incontinence. Conclusion: The knowledge and practices of practitioners working at a primary healthcare level in the Western Cape are not congruent with NICE 2013 guidelines. Clinical implications: Data can be used to inform intervention planning to address urinary incontinence management at a primary healthcare level in the Western Cape.